ASA-graphs for efficient data representation and processing - Horzyk, Adrian; Bulanda, Daniel; Starzyk, Janusz A. (Zielona Góra: Uniwersytet Zielonogórski)
Fast discovering of various relationships in data is an important feature of modern data mining, cognitive, knowledge-based, and explainable AI systems, including deep neural networks. The ability to represent a rich set of relationships between stored data and objects is essential for fast inferences, finding associations, representing knowledge, and extracting useful patterns or other pieces of information.
Keywords: self-balancing trees; self-sorting trees; self-aggregating data structures; associative structures; graphs; data access efficiency; representation of relationships